Pengaruh Beban Kerja, Pelatihan Kerja, dan Kemandirian Karyawan terhadap Produktivitas Kerja Karyawan CV. Ulur Wiji Muda Berdaya di Kemlagi Kabupaten Mojokerto - Suryansyah, Ismu Abdi; Setyaasih, Setyaasih; Cahyani, Diah; Muzrifah, Risa Amalia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to identify the variables affecting the productivity of employees at CV. Ulur Wiji Muda Berdaya Mojokerto, whether partially, simultaneously, or dominantly. The study uses a quantitative approach. The research method employed is a survey method, with a questionnaire as the data collection tool and a sampling technique called saturated sampling. The effects of workload, job training, and independence also influence and determine the effectiveness of their impact on productivity. This is consistent with the respondent's research in this study, which indicates that workload plays a crucial role in employee productivity at CV. Ulur Wiji through several indicators and is stated to have a positive effect on increasing employee productivity. In the job training process at CV. Ulur Wiji, the variable values positively influence the increase in employee productivity through several indicators. The impact of employee independence at CV. Ulur Wiji shows that the variable values positively influence the increase in employee productivity through several indicators.